2014
DOI: 10.1177/0165025414544231
|View full text |Cite
|
Sign up to set email alerts
|

Anticipating their future

Abstract: Adolescent future values – beliefs about what will matter to them in the future – may shape their adult behavior. Utilizing a national longitudinal British sample, this study examined whether adolescent future values in six domains (i.e., family responsibility, full-time job, personal responsibility, autonomy, civic responsibility, and hedonistic privilege) predicted adult social roles, civic behaviors, and alcohol use. Future values positively predicted behaviors within the same domain; fewer cross-domain ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 60 publications
(99 reference statements)
0
8
0
Order By: Relevance
“…Our results underscore that adolescents are paying attention to national and world events. Trends in adolescents' social issues are informative in light of evidence that youths' political views and behavior may be shaped in lasting ways by the concerns they develop in adolescence (Davis, 2004;Finlay, Wray-Lake, Warren, & Maggs, 2015;Schuman & Corning, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Our results underscore that adolescents are paying attention to national and world events. Trends in adolescents' social issues are informative in light of evidence that youths' political views and behavior may be shaped in lasting ways by the concerns they develop in adolescence (Davis, 2004;Finlay, Wray-Lake, Warren, & Maggs, 2015;Schuman & Corning, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Reynolds and Burge (2008) reported a similar relationship between expectations to finish college and subsequent college graduation, which contributed to greater educational attainment for women in particular. With regard to family formation, Finlay and colleagues (2014) found that adolescents who reported believing that family would be important to them as adults were more likely to be married and have children, but less likely to be working in early adulthood. Likewise, Johnson & Mortimer (2000) reported that, in addition to predicting educational and occupational outcomes, adolescent expectations related to education, work, and family roles predicted delayed entry into cohabitation for both genders in young adulthood, and delayed entry into marriage for women.…”
Section: Adolescents’ Expectations Predict Their Adult Outcomesmentioning
confidence: 99%
“…Consistent with these findings, three patterns have been found across a variety of studies and samples: a group of young people who transition out of education and into work and/or family formation (i.e., partnering and parenting) early, a group that delays some of the transitions to adulthood in favor of higher education, and a group that enters the workforce relatively early without family formation. Given that adolescent future-oriented cognitions have been shown to predict young adult outcomes (Beal & Crockett, 2010; Finlay, Wray-Lake, Warren, & Maggs, 2014; Guo, Marsh, Morin, Parker, & Kaur, 2015; Khattab, 2015; Mello, 2008; 2009; Mike Vuolo, Jeylan T. Mortimer, & Jeremy Staff, 2014) pathways to adulthood may offer an important framework for understanding how adolescent expectations fit together across domains.…”
Section: Observed Patterns In the Transition To Adulthoodmentioning
confidence: 99%
“…To initiate the steps of becoming engaged contributors to society, however, adolescent youth must first be presented the opportunity to become involved in civic engagement activities (Hart & Atkins, 2002;Langston, 1987). If adolescent youth miss the opportunity to become civically involved, their civic capacities in adulthood could be diminished (Finlay, Wray-Lake, Warren, & Maggs, 2014).…”
Section: Introduction and Conceptual Frameworkmentioning
confidence: 99%
“…However, the simple act of participating in civic engagement activities does not necessarily maximize civic responsibility development (Bringle & Hatcher, 1999;Finlay et al, 2014). A critical component to successful, meaningful, and developmentally constructive civic engagement involves time for youth to critically process the civic engagement experience using structured postactivity reflection (Billig, 2000;Mitchell et al, 2015).…”
Section: Introduction and Conceptual Frameworkmentioning
confidence: 99%